Pengaruh Kepuasan Kerja, Work Life Balance dan Pengakuan Terhadap Keterlibatan Kerja Karyawan - Muhammad Adhitya Handaka; Mohammad Fauzan (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of the study was to analyze and explain the effect of (1) job satisfaction on employee work engagement, (2) work-life balance on employee work engagement (3) recognition of employee work involvement of PT Jaya Arnikon in the city of Semarang. This type of research is explanatory research. The sample was 102 employees. Data collection uses a questionnaire using a google form, which is then sent to each respondent. Data analysis uses multiple linear regression. For the purpose of analysis, instrument tests are carried out; model test and hypothesis test with the help of SPSS software. The findings of the research results were (1) Job satisfaction has a positive effect on employee work involvement (2) Work-life balance has a positive effect on employee work involvement (3) Recognition has a positive effect on employee work engagement of PT Jaya Arnikon. Keywords: Job Satisfaction; Work-Life Balance; Recognition